BAWAH RESERVE: EKSPLORASI KEMUNGKINAN PARIWISATA MEWAH YANG BERKELANJUTAN DI PULAU ANAMBAS - Ramadita, Salsabila (JURNAL KEPARIWISATAAN, 2024)
This article publication aims to examine the Bawah Reserve’s efforts towards sustainability, a luxury resort located on remote and marine conservation area Anambas Island, Indonesia. Its appeal is based on luxury, but it also offers insights into the small island’s nature and community development. By analyzing the content based on the grounded theory approach, this study sheds light on the opportunities that arise when striving for both opulence and environmental responsibility in the context of tourism. The paper attempts to address how eco-luxury is projected by management and perceived by customers and community. A qualitative study was adopted, and the findings identify four themes: Sustainable Management, Sustainable Socioeconomic Benefits, Cultural Heritage and Reduced Cultural Impacts, and Environmental Protection and Conservation. The findings of sustainable tourism practices in Bawah Reserve, such as tourism packages based on natural conservation and community empowerment as well as eco-friendly infrastructure and operations add to the literature review and case studies in the field of sustainable luxury tourism, the majority of which focus on Bali or Maldives. This study offers insights for achieving a harmonious balance between luxury tourism and sustainability on a remote island within the Indonesian context.